2019
DOI: 10.1097/olq.0000000000001064
|View full text |Cite
|
Sign up to set email alerts
|

A Co-Located Continuity Clinic Model to Address Healthcare Needs of Women Living Unhoused With Opioid Use Disorder, Who Engage in Transactional Sex in North Seattle

Abstract: This is a review of the first 50 patients attending a colocated continuity clinic with harm reduction services to women experiencing homelessness in north Seattle. Among those tested, patients had high rates of curable sexually transmitted infections (44%), injection opioid use (36%), transactional sex (69%), unintended pregnancy (10%), and human immunodeficiency virus infections (10%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…26 Models of care, such as community clinics colocated with other services or peer-based clinics, may have more success engaging this population. 9,17 These results add to prior studies, suggesting that PWES are at higher risk for poor HIV and HCV outcomes. In our study, 67% of PWES reported HIV viral suppression compared with 73% in those who never exchanged sex.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…26 Models of care, such as community clinics colocated with other services or peer-based clinics, may have more success engaging this population. 9,17 These results add to prior studies, suggesting that PWES are at higher risk for poor HIV and HCV outcomes. In our study, 67% of PWES reported HIV viral suppression compared with 73% in those who never exchanged sex.…”
Section: Discussionsupporting
confidence: 65%
“…In contrast, a prior study in Colorado Springs estimated that 80% of all “female prostitutes” were seen in the health department STD clinic during 1970 to 1990. One factor that likely contributed to this was health department outreach efforts, including “recruiting efforts … where and when prostitutes work.” 26 Models of care, such as community clinics colocated with other services or peer-based clinics, may have more success engaging this population 9,17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pilot program in Seattle demonstrated feasibility, acceptability, and confirmed the high interest in SRH services among WWID [63]. Another novel community partnership clinic model in Seattle reported a high unmet need for STI and reproductive health services in homeless women who engage in transactional sex and IDU [64]. Women attending a harm reduction program in Sweden indicated that SRH services were the most valued part of the package [65].…”
Section: Strategies To Address Sexual Health Among People Who Inject ...mentioning
confidence: 99%
“…Patients at the SHE Clinic reflect the unhoused population’s high rates of injection drug use, exchange sex, unplanned pregnancy, and sexually transmitted infections. 6 In this cohort study, we evaluated the association between use of the SHE Clinic and the frequency of nonemergent emergency department (ED) visits among women living unhoused who exchange sex and inject drugs.…”
Section: Introductionmentioning
confidence: 99%